1998
DOI: 10.1126/science.279.5357.1672
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Upper Atmosphere of Mars: In Situ Accelerometer Measurements from Mars Global Surveyor

Abstract: The Mars Global Surveyor (MGS) z -axis accelerometer has obtained over 200 vertical structures of thermospheric density, temperature, and pressure, ranging from 110 to 170 kilometers, compared to only three previous such vertical structures. In November 1997, a regional dust storm in the Southern Hemisphere triggered an unexpectedly large thermospheric response at mid-northern latitudes, increasing the altitude of thermospheric pressure surfaces there by as much as 8 kilometers and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
237
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(258 citation statements)
references
References 27 publications
20
237
1
Order By: Relevance
“…In particular, the vertical thermal structure of the upper atmosphere has been sampled many times, but only in limited latitude/local time zones, and mostly during solar minimum to moderate conditions (see review by . Existing temperature profiles include those from: (a) Viking Landers 1 and 2 entry accelerometers on the dayside based on mass density scale heights (Seiff and Kirk 1977), (b) Viking Landers 1 and 2 Upper Atmosphere Mass Spectrometer (UAMS) on the dayside (Nier and McElroy 1977), (c) Mars Global Surveyor (MGS), Mars Odyssey (MO), and Mars Reconnaissance Orbiter (MRO) aerobraking accelerometers for both dayside and nightside (e.g., Keating et al 1998Keating et al , 2006Keating et al , 2008, and (d) Mars Express SPICAM (mostly nightside) inferred from stellar occultations McDunn et al 2010). In addition, vertical profiles of key dayglow emissions observed by Mariners 6, 7, 9, and Mars Express have been used to extract temperatures, especially topside (exosphere) values (e.g.…”
mentioning
confidence: 99%
“…In particular, the vertical thermal structure of the upper atmosphere has been sampled many times, but only in limited latitude/local time zones, and mostly during solar minimum to moderate conditions (see review by . Existing temperature profiles include those from: (a) Viking Landers 1 and 2 entry accelerometers on the dayside based on mass density scale heights (Seiff and Kirk 1977), (b) Viking Landers 1 and 2 Upper Atmosphere Mass Spectrometer (UAMS) on the dayside (Nier and McElroy 1977), (c) Mars Global Surveyor (MGS), Mars Odyssey (MO), and Mars Reconnaissance Orbiter (MRO) aerobraking accelerometers for both dayside and nightside (e.g., Keating et al 1998Keating et al , 2006Keating et al , 2008, and (d) Mars Express SPICAM (mostly nightside) inferred from stellar occultations McDunn et al 2010). In addition, vertical profiles of key dayglow emissions observed by Mariners 6, 7, 9, and Mars Express have been used to extract temperatures, especially topside (exosphere) values (e.g.…”
mentioning
confidence: 99%
“…Although the dust spread farther on subsequent orbits, it seemed to fade into a background dustiness that persisted for several weeks afterward. At the altitude of the spacecraft (124 km), the dust storm caused orbit-to-orbit variations in atmospheric density by factors of 2 or more (41).…”
Section: Reportsmentioning
confidence: 99%
“…The neutral temperature increases with altitude to an overall maximum value (200-350 K) and then becomes constant. The thermosphere is subject to in situ forcing due to gravity/planetary waves and solar thermal tides (Keating et al 1998;Bougher et al 2014). The dynamics of the thermosphere are still poorly constrained by data.…”
Section: The Vertical Structure Of the Upper Atmosphere Of Marsmentioning
confidence: 99%
“…One of the most intriguing effects is due to dust storms: during these events, the atmospheric opacity increases, and the lower atmosphere is heated, and expands. The density of the thermosphere increases (Keating et al 1998), and the altitude of the peak electron density can increase by up to about 30 km (Wang and Nielsen 2003). Withers and Pratt (2013) have shown that the upper atmospheric regions can be affected globally, and at altitudes as high as 160 km.…”
Section: Variability Of the Upper Atmospherementioning
confidence: 99%